(untitled) (Al Basirah, 2024)
Arnold Joseph Toynbee (d. 1975), influenced by Ibn Khaldun, is highly regarded among contemporary Muslim scholars. His work, "A Study of History," examines the rise and fall of civilizations, focusing on the factors leading to the decline of Islamic civilization, notably the lack of unity within the Muslim Ummah. This research aims to provide a brief overview of Toynbee’s life and his philosophical influences, specifically Ibn Khaldun. The methodology involves an analysis of Toynbee’s writings and their reception among Muslim historians. Key findings highlight critical factors contributing to disunity, such as political fragmentation, socio-economic disparities, and external interventions. Toynbee’s theories on the cyclical nature of civilizations and the role of religion are explored to understand these dynamics. The study concludes with suggestions for fostering a cohesive Ummah in the modern era, emphasizing the need for a unified vision, stronger inter-community relations, and strategic leadership.